ANALISIS PERILAKU KONSUMEN DALAM MEMILIH PRODUK KOSMETIK YANG RAMAH LINGKUNGAN - Agung Edy Wibowo (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2017)
This research has mainly aimed to know and analyze customer behavior in selecting of green marketing cosmetics products. Sample in this research were taken using purposive sampling method. There were 114 respondent in this research. The usage of regression formula can be done as all of classical assumption test had been through and qualified. All over the test shown that social class influence significantly toward buying decision at the level of significance 0.000 less than 0.05. The secondary result of this research found that group of reference has influence significantly toward buying decision at the level of significance 0.001 less than 0.05. The third result shown us that family has influence significantly toward buying decision at the level of significance 0.000 less than 0.05. Meanwhile result for simultaneous test shown that social class, group of reference and family, have influence significantly toward buying decision. It has been proved at the level of significance 0.000 less than 0.05. All of these imply that all of hypotheses in this research can be proved, or accepted